An improved control algorithm for Series Hybrid Active Power Filter based on SOGI-PLL under dynamic load conditions. (July 2021) - Pazhanimuthu, C.; Baranilingesan, I.; Karthick, Alagar
Abstract: An expansion in the single-phase and non-linear load of domestic, industries and small businesses scale utilize this 3-phase distribution, resulting in an unwanted harmonic current flowing through the grid. The quality of the current produced is too noisy for our liking results in reduces the system performance and power quality issues. Hence, in this study, an improved control algorithm is suggested for Series Hybrid Active Power Filter (SHAPF) performs more accurate dynamic compensation under distorted changes in load. The proposed Second-Order Generalized Integrator (SOGI) controller accurately identifies the phase angle variation under the operation of non-linear and single-phase loads in a three-phase system. Thus, it eliminates harmonics in the system; it is having the ability to control injected and source voltages. It also focuses on harmonics, voltage sag, swell, voltage unbalance, and neutral current issues throughout the transformer's life. To prove that the system is functional, the solar photovoltaic system is put in place. The solar power interfaced with the DC-link compensated for the issues of short and long-term voltage interruptions effectively. The prescribed controller's performance is examined in MATLAB 2020b/Simulink environment and hardware prototype model under dynamic load conditions in a 3-phase 4-wire distributed system. The experimental results reveal that the SOGI controller diminishes the Total Harmonic Distortion (THD) value of around 30%, which improves the system's stability and performance. Highlights: Series Hybrid Active Power Filter improved algorithm is investigated. SOGI controller with SOGI-PLL is proposed. Investigated with non-linear and single-phase loads in a three-phase system. Total harmonic distortion is reduced up to 30%.